A Literature Review: The Relationship of Family Resilience with The Incidence of Stunting in Children - Laili Rahayuwati; Alfiani Hidayanti; Arlette Suzy Puspa Pertiwi; Vira Amelia; Don Prisno; Myra D. Oruga (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2025)
Introduction: family is the factor that influences the growth of children in a family. Stunting is a condition that must be of special concern because it can resistor the physical development and mental of children. The family's role and function in increasing family resilience is very needed in the compliance nutritional status of children under five. Objectives: The aim of this study was to see the relationship between family resilience and the incidence of stunting in children. Methods: This study used a literature review method, and the literature search procedure was conducted using databases such as PubMed and Google Scholar. Keywords included